Crisis communication management strategies: a comparative analysis of corporate responses in global emergencies - Asmara Juana Suhardi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to analyze the crisis communication strategies implemented by companies in various industry sectors during global emergency situations. This study conducts a comparative analysis of corporate crisis communication responses in various industry sectors and geographical regions to identify the most effective strategies in dealing with global crises, such as the COVID-19 pandemic, natural disasters, and economic crises. This study uses a mixed methods approach, which involves qualitative and quantitative analysis. The qualitative approach was conducted through in-depth case studies of five multinational companies in the energy, technology, and healthcare sectors, selected based on the significance of their crisis responses. Data was collected through semi-structured interviews with corporate communications managers and content analysis of media statements as well as social media. Quantitative analysis was carried out using a survey involving 200 respondents to measure public perception of the effectiveness of crisis communication. The data was analyzed using a comparative approach to identify key patterns in the communication strategies implemented by the company. The results of the study show that companies that implement a transparent, consistent, and empathetic-centered communication strategy are more successful in maintaining the public image and gaining customer trust. The comparative analysis also revealed significant differences in crisis response by industry sector and geographic region. Companies in the technology sector, for example, rely more on social media to maintain fast and interactive communication, while companies in the energy sector tend to use formal press statements to handle crises. This research emphasizes the importance of flexibility and adaptability in crisis communication strategies, as well as the need to consider the context of the industry and geographic region when designing a crisis response. The results of this study are expected to provide guidance for companies in improving their crisis communication readiness, especially in facing future global crises.